2017
DOI: 10.4149/neo_2017_505
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid derivative SZC014 inhibit cell proliferation and induce apoptosis of human breast cancer cells in a ROS-dependent way

Abstract: Oleanolic acid (OA) and its derivatives are a novel emerging class of compounds. Although OA exhibits potent anticancer and anti-inflammatory function, the potential effect of its new derivatives (SZC014) in human breast cancers has not been understood yet. In this investigation, we demonstrated the anticancer effect of SZC014, a novel OA derivative and identified the possible mechanisms by which SZC014 induced MCF-7 cell death. The biological functions of SZC014 were validated by MTT, migration and colony for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…In this context, we report here that the induced apoptosis by the synthesized complexes was proportionally associated with a significant increase in ROS production. Previous observations support our current results; these studies showed that cancer cell proliferation inhibition and apoptosis induction are mediated by oxidative stress induction [ 42 ]. Importantly, the induction of oxidative stress by metal-based drugs is believed to mediate the activation of autophagy-associated cell death pathway markers [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this context, we report here that the induced apoptosis by the synthesized complexes was proportionally associated with a significant increase in ROS production. Previous observations support our current results; these studies showed that cancer cell proliferation inhibition and apoptosis induction are mediated by oxidative stress induction [ 42 ]. Importantly, the induction of oxidative stress by metal-based drugs is believed to mediate the activation of autophagy-associated cell death pathway markers [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…With Notch1 knockdown, Ole induced LC3B proteins changing was recovery in HaCaT cell psoriasis model. As a natural pentacyclic triterpenoid, Ole has been reported to exert antitumor and anti-inflammatory effects (Wang et al 2019;Abdelmageed et al 2017), and has been shown to be effective in the treatment of multiple types of tumor (Chu et al 2017;Dong et al 2020;Han et al 2021). The results of the present study revealed that Ole intervention could effectively inhibit the abnormal proliferation of HaCaT cells induced by IL-22 stimulation and promote their apoptosis, which may subsequently inhibit the development of psoriasis.…”
Section: Expression Levels Of Lc3b Protein In Hacat Cell Psoriasis Modelmentioning
confidence: 54%
“…23 The derivatives of oleanolic acid have been reported for the treatment of pancreatic cancer, 24 and oleanolic acid saponins have shown significant antimicrobial properties, 25 and the combination of oleanolic acid with hypocrellin A has been reported for the treatment of hepatocellular carcinoma diseases, 26 and oleanolic acid derivative SZC014 has exhibited anticancer activity. 27 Oleanolic acid has shown antidiabetic, 28,29 and hepatoprotective activities, 30,31 which may establish the use of H. umbellata as antidiabetic by the local inhabitants in Nigeria.…”
Section: Resultsmentioning
confidence: 99%